Quality analysis of dragon fruit yoghurt for dyslipidemic patients - Kasmiyetti, Kasmiyetti; Hasneli, Hasneli; Nabiella, Nabiella; Febiola, Febiola (Jurnal Gizi dan Dietetik Indonesia (Indonesian Journal of Nutrition and Dietetics), 2025)
ABSTRAK Latar Belakang:  Penyakit kardiovaskular merupakan penyebab kematian nomor satu di dunia dengan faktor risikonya yaitu profil lipid dalam batas yang tidak normal.Tujuan: Tujuan penelitian ini untuk mengetahui pengaruh pemberian probiotik yoghurt sari buah naga terhadap kadar profil lipid penderita dislipidemia pada pegawai Poltekkes Kemenkes Padang Kampus I dan II.Metode: Desain penelitian adalah quasi eksperimen with pre-post test design, dengan membandingkan kadar lipid profile sebelum dengan setelah diberikan perlakuan. Total sampel berjumlah 30 orang, dipilih dengan menggunakan purposive sampling. Pengumpulan data dilakukan selama 21 hari, dengan pemberian yoghurt sebanyak 1 botol per hari, disiang hari, melakukan recall, pengisian kuesioner dari pemeriksaan laboratorium profil lipid (Cholesterol, HDL, LDH and triglyceride). Uji statistik yang digunakan adalah T-Test dependent dan independent.Hasil: Dari hasil penelitian terdapat perbedaan yang bermakna pada kadar kolesterol total responden awal dan akhir sampel perlakuan (p < 0,05), dan terdapat perbedaan yang bermakna pada kadar trigliserida responden awal dan akhir sampel perlakuan  (p < 0,05). Tidak ada perbedaan yang bermakna kadar lipid profile awal dengan akhir sampel kontrol  (p > 0,05). Tidak ada perbedaan yang bermakna kadar lipid profile akhir sampel perlakuan  dengan  sampel kontrol  (p > 0,05). Didapatkan kandungan zat gizi vitamin B2, B3, B6, B7, C dan serat dalam 100 mg yoghurt sari buah naga, yang beberapa diantaranya memiliki hubungan dengan perubahan kadar lipid profile.Kesimpulan: Disarankan kepada peneliti selanjutnya untuk melanjutkan penelitian dengan jumlah sampel yang lebih banyak dan uji kandungan zat aktif produk sehingga dapat dijadikan salah satu minuman alternatif untuk penderita dislipidemia. Kata Kunci: dislipidemia, yoghurt, sari buah naga  ABSTRACTBackground: Cardiovascular disease is the number one cause of death in the world with a risk factor, namely a lipid profile within abnormal limits.Objectives: The purpose of this study was to determine the effect of giving dragon fruit yoghurt probiotics on the profile of dyslipidemia sufferers in the Health Polytechnic of the Ministry of Health, Padang Campus I and II.       Methods: The research design was a quasi-experimental with pre-post test design, by comparing the levels of lipid profile before and after being given treatment. The total sample size is 30 people, selected using purposive sampling. Data collection was carried out for 21 days, by giving 1 bottle of yoghurt per day, during day by recalling and filling out questionnaires from laboratory tests (lipid profile). The statistical test used is T-Test dependent and independent.      Results: From the results of the study, there was a significant difference in the total cholesterol levels of the initial and final respondents of the treatment sample (p < 0.05), and there was a significant difference in the triglyceride levels of the initial and final respondents of the treatment sample (p < 0.05). There was no significant difference between the initial and final profile of the control sample (p > 0.05). There was no significant difference in the final profile of the treatment sample with the control sample (p > 0.05). It was found that the nutritional content of vitamins B2, B3, B6, B7, and C and fiber in 100 mg of dragon fruit juice yoghurt, some of which have a relationship with changes in lipid profile levels.      Conclusions: It is recommended that further researchers continue research with a larger number of samples and test the product's active substance content so that it can be used as an alternative drink for people with dyslipidemia. Keywords: dyslipidemia, yoghurt, dragon fruit juiceReceived: 23 Jan 2025; Revised: 06 Sep 2024; Accepted: 24 Jan 2025; Available online: 30 Mar 2025; Published: 30 Mar 2025